2019
DOI: 10.1007/s10803-019-04102-0
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions and Symptom Severity in an Italian Sample of Intellectually Able Preschoolers with Autism Spectrum Disorder

Abstract: A novel battery (BAFE; Valeri et al., 2015) was used in order to assess three Executive Function (EF) abilities (working memory, inhibition and shifting) in a sample of 27 intellectually able preschoolers with Autism Spectrum Disorders (ASD) compared with 27 typically developing children matched on age and nonverbal IQ. Differences in EF skills were analyzed in participants with distinct ASD symptom severity. Children with ASD performed worse than typical controls on both set-shifting and inhibition, but not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…However, recent researches showed that also executive functioning, assessed in preschoolers [i.e. Valeri et al, 2019], are predictors of adaptive level in a 12 years follow‐up [Kenny, Cribb, & Pellicano, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent researches showed that also executive functioning, assessed in preschoolers [i.e. Valeri et al, 2019], are predictors of adaptive level in a 12 years follow‐up [Kenny, Cribb, & Pellicano, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…The deficit in inhibition has been associated with the inefficient ability to regulate RRBs (Turner, 1997). This hypothesis was supported by Valeri and coworkers, who found that children with ASD committed more errors to suppress responses in comparison to typically developed children (Valeri et al., 2019). Similar findings have been documented in adults (Van Eylen et al., 2015).…”
Section: Etiology Of Rrbs In Asdmentioning
confidence: 67%
“…However, existing research does not point to the universal pro le of weaknesses in EF that we found in our study. For example, other studies have also found signi cant EF differences in preschools with ASD and typically developing preschoolers in the domain of shifting and inhibition but not on visual-spatial working memory tasks (Valeri et al, 2020). In a study that used the BRIEF-P for the assessment of EF, signi cant differences between preschoolers with ASD and typically developing children were again found on the subscales: inhibition and shifting but not on the subscale working memory (Carotenuto et al, 2019).…”
Section: Discussionmentioning
confidence: 96%